Genomic and Ecogenomic Characterization of Proteus mirabilis Bacteriophages - Alves, Diana R.; Nzakizwanayo, Jonathan; Dedi, Cinzia; Olympiou, Chara; Hanin, Aurélie; Kot, Witold; Hansen, Lars; Lametsch, Rene; Gahan, Cormac G. M.; Schellenberger, Pascale; Ogilvie, Lesley A.; Jones, Brian V. (Frontiers in Microbiology, 2019)
Proteus mirabilis often complicates the care of catheterised patients through the formation of crystalline biofilms which block urine flow. Bacteriophage therapy has been highlighted as a promising approach to control this problem, but relatively few phages infecting P. mirabilis have been characterised. Here we characterise five phages capable of infecting P. mirabilis, including those shown to reduce biofilm formation, and provide insights regarding the wider ecological and evolutionary relationships of these phages. Transmission Electron Microscopy (TEM) imaging of phages vB_PmiP_RS1pmA, vB_PmiP_RS1pmB, vB_PmiP_RS3pmA and vB_PmiP_RS8pmA showed that all share morphologies characteristic of the Podoviridae family. The genome sequences of vB_PmiP_RS1pmA, vB_PmiP_RS1pmB and vB_PmiP_RS3pmA showed these are species of the same phage differing only by point mutations, and are closely related to vB_PmiP_RS8pmA. Podophages characterised in this study were also found to share similarity in genome architecture and composition to other previously described P. mirabilis podophages (PM16, PM75). In contrast, vB_PimP_RS51pmB showed morphology characteristic of the Myoviridae family, with no notable similarity to other phage genomes examined. Ecogenomic profiling of all phages revealed no association with human urinary tract viromes, but sequences similar to vB_PimP_RS51pmB were found within human gut and human oral microbiomes. Investigation of wider host-phage evolutionary relationships through tetranucleotide profiling of phage genomes and bacterial chromosomes, indicated vB_PimP_RS51pmB has a relatively recent association with Morganella morganii and other non-Proteus members of the Morganellaceae family. Subsequent host range assays confirmed vB_PimP_RS51pmB can infect M. morganii.